Afferent and motoneuron activity in response to single neuromast stimulation in the posterior lateral line of larval zebrafish - Haehnel-Taguchi, Melanie (American Physiological Society, 2014)
The lateral line system of fishes contains mechanosensory receptors along the body surface called neuromasts, which can detect water motion relative to the body. The ability to sense flow informs many behaviors, such as schooling, predator avoidance, and rheotaxis. Here, we developed a new approach to stimulate individual neuromasts while either recording primary sensory afferent neuron activity or swimming motoneuron activity in larval zebrafish (Danio rerio). Our results allowed us to characterize the transfer functions between a controlled lateral line stimulus, its representation by primary sensory neurons, and its subsequent behavioral output. When we deflected the cupula of a neuromast with a ramp command, we found that the connected afferent neuron exhibited an adapting response which was proportional in strength to deflection velocity. The maximum spike rate of afferent neurons increased sigmoidally with deflection velocity, with a linear range between 0.1 and 1.0 μm/ms. However, spike rate did not change when the cupula was deflected below 8 μm, regardless of deflection velocity. Our findings also reveal an unexpected sensitivity in the larval lateral line system: stimulation of a single neuromast could elicit a swimming response which increased in reliability with increasing deflection velocities. At high deflection velocities, we observed that lateral line evoked swimming has intermediate values of burst frequency and duty cycle that fall between electrically evoked and spontaneous swimming. An understanding of the sensory capabilities of a single neuromast will help to build a better picture of how stimuli are encoded at the systems level and ultimately translated into behavior.